Spatially resolved measurement of transverse surface acoustic waves for the investigation of elastic properties - Behme, G; Hesjedal, T; Chilla, E; Frolich, H (John Wiley and Sons Ltd, 1999)
This paper reports new developments in the field of spatially resolved surface acoustic wave (SAW) analysis. With scanning acoustic force microscopy (SAFM) the investigation of SAW phenomena with lateral resolution of the scanning force microscope became possible. This technique was limited to SAW modes with an out-of-plane oscillation component. Recently, we demonstrated that purely in-plane polarized SAWs can also be investigated by using a non-linear coupling to the cantilever's torsional movement. Now it is possible to measure the SAW phase velocity dispersion for any given SAW polarization. We used SAFM for investigation of the layered system SiO2 on ST-cut quartz.